Keanekaragaman Capung (Odonata) di Koridor Sungai Perkotaan Pasca-Restorasi Riparian: Pendekatan eDNA Metabarcoding - Janwadi, Andi Pratama; Lestari , Nilam Cahya (Lembaga Publikasi Ilmiah Nusantara, 2025)
Dragonflies (Odonata) are widely recognized as bioindicators of freshwater ecosystem quality, yet conventional morphological observations often face limitations in species identification. Environmental DNA (eDNA) metabarcoding offers a more sensitive and efficient approach to assess community responses to environmental changes. This study aimed to analyze the diversity of Odonata in an urban river corridor following riparian restoration using an eDNA metabarcoding approach. Water samples were collected from several restored riparian sites, followed by DNA extraction and amplification of the Cytochrome Oxidase I (COI) gene. Sequencing data were processed through bioinformatics pipelines for species identification and diversity analysis. The results showed that eDNA metabarcoding detected a greater number of Odonata species compared to conventional field observations. The Shannon-Wiener diversity index ranged from moderate to high (H’ = 2.1–2.8), with dominant species belonging to the families Libellulidae and Coenagrionidae. Moreover, sensitive indicator species were identified, indicating improved habitat quality after restoration. In conclusion, eDNA metabarcoding proved to be an effective tool for detecting Odonata diversity and can serve as a reliable biomonitoring method to evaluate the success of riparian restoration in urban river ecosystems.